Constitutive and Companion Cell-Specific Overexpression of AVP1, Encoding a Proton-Pumping Pyrophosphatase, Enhances Biomass Accumulation, Phloem Loading, and Long-Distance Transport . Issue 1 (3rd November 2015) - Khadilkar, Aswad S.; Yadav, Umesh P.; Salazar, Carolina; Shulaev, Vladimir; Paez-Valencia, Julio; Pizzio, Gaston A.; Gaxiola, Roberto A.; Ayre, Brian G.
Abstract : H + -pumping pyrophosphatases appear to function in companion cells to increase phloem loading and long-distance transport, leading to more robust plants with enhanced growth. Abstract: Plant productivity is determined in large part by the partitioning of assimilates between the sites of production and the sites of utilization. Proton-pumping pyrophosphatases (H + -PPases) are shown to participate in many energetic plant processes, including general growth and biomass accumulation, CO2 fixation, nutrient acquisition, and stress responses. H + -PPases have a well-documented role in hydrolyzing pyrophosphate (PPi ) and capturing the released energy to pump H + across the tonoplast and endomembranes to create proton motive force (pmf ). Recently, an additional role for H + -PPases in phloem loading and biomass partitioning was proposed. In companion cells (CC s) of the phloem, H + -PPases localize to the plasma membrane rather than endomembranes, and rather than hydrolyzing PPi to create pmf, pmf is utilized to synthesize PPi . Additional PPi in the CC s promotes sucrose oxidation and ATP synthesis, which the plasma membrane P-type ATPase in turn uses to create more pmf for phloem loading of sucrose via sucrose-H + symporters. To test this model, transgenic Arabidopsis ( Arabidopsis thaliana ) plants were generated with constitutive and CC -specific overexpression of AVP1, encoding type 1 ARABIDOPSIS VACUOLAR PYROPHOSPHATASE1. Plants with both constitutive and CC -specific overexpression accumulated more biomass in shoot and root systems. 14 C-labeling experiments showed enhanced photosynthesis, phloem loading, phloem transport, and delivery to sink organs. The results obtained with constitutive and CC -specific promoters were very similar, such that the growth enhancement mediated by AVP1 overexpression can be attributed to its role in phloem CC s. This supports the model for H + -PPases functioning as PPi synthases in the phloem by arguing that the increases in biomass observed with AVP1 overexpression stem from improved phloem loading and transport.